The Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd005011.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant factor VIIa for the prevention and treatment of bleeding in patients without haemophilia

Abstract: The version presented here may differ from the published version. If citing, you are advised to consult the published version for pagination, volume/issue and date of publication Recombinant factor VIIa for the prevention and treatment of bleeding in patients without haemophilia (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(25 citation statements)
references
References 78 publications
0
24
0
1
Order By: Relevance
“…4,5,62 The half-life of factor VII is approximately 6 hours, whereas that of factor II is 60 to 72 hours. 54 Moreover, the half-life of rFVIIa may be even shorter than 6 hours owing to the increased volume of distribution when compared with the longer plasmaderived factor VII.…”
Section: 61mentioning
confidence: 99%
See 2 more Smart Citations
“…4,5,62 The half-life of factor VII is approximately 6 hours, whereas that of factor II is 60 to 72 hours. 54 Moreover, the half-life of rFVIIa may be even shorter than 6 hours owing to the increased volume of distribution when compared with the longer plasmaderived factor VII.…”
Section: 61mentioning
confidence: 99%
“…4,5,62 A 2011 Cochrane database review of 3500 patients across 25 randomized controlled trials (nonsurgical as well as noncardiac and cardiac surgery patients) found modest blood loss after rFVIIa administration either for prophylactic or therapeutic means. 4 Eleven of the 25 trials (n = 2366) involving therapeutic use of rFVIIa found an increase in the thromboembolic events (relative ratio [RR], 1.21; 95% confidence interval, 0.93-1.58). Thirteen trials (n = 1137) assessing the prophylactic use also found a trend toward thromboembolisms (RR, 1.32; 95% confidence interval, 0.84-2.06).…”
Section: 61mentioning
confidence: 99%
See 1 more Smart Citation
“…46 -48 Systemic infusion of certain coagulation factors (eg, activated factor VII, prothrombin complex, factor XIII, and fibrinogen) has also been investigated as means to reduce blood loss (occasionally used in conjunction with point-ofcare coagulation tests), and the verdict on the safety and efficacy of these agents for this indication is still unclear. 46 Particularly, recent meta-analyses of clinical trials have questioned the efficacy of offlabel recombinant activated factor VII in reducing bleeding 49 and concluded that the off-label use at high doses increases the risk of thromboembolic events. 50 Another systemic approach to minimize blood loss is avoiding hypothermia (if not otherwise indicated), as hypothermia can adversely affect platelet function and result in increased blood loss.…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…[30][31][32] Early termination of the randomised controlled CONTROL trial 33 was prompted by a futility analysis owing to lower-than-projected mortality rates. Having primarily set out to compare 30-day mortality, this study of rFVIIa as an adjunct to direct haemostasis in major trauma identified that rFVIIa reduced blood product use significantly, without increasing adverse or thrombotic events.…”
Section: Prevention and Correction Of Coagulopathymentioning
confidence: 99%